2022
DOI: 10.1177/00307270221082113
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to attain the same soil organic matter content in arable agricultural soils as under natural vegetation?

Abstract: Clearing natural vegetation to establish arable agriculture (cropland) almost invariably causes a loss of soil organic carbon (SOC). Is it possible to restore soil that continues in arable agriculture to the pre-clearance SOC level through modified management practices? To address this question we reviewed evidence from long-term experiments at Rothamsted Research, UK, Bad Lauchstädt, Germany, Sanborn Field, USA and Brazil and both experiments and surveys of farmers’ fields in Ethiopia, Australia, Zimbabwe, UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…A recent study in Almora, Uttarakhand (Meena et al, 2018) also revealed a higher accumulation of SOC, down to a depth of 45 cm, in FLs as compared to cultivated lands. The observed build up of SOC content in the natural grasslands (FL; Figure 2d) could also be due to its continuous incorporation through root litter (Powlson et al, 2022). Additionally, these soils are rarely disturbed by cultural practices that are otherwise followed in orchard soils (e.g., monsoon or winter plowing) of the present study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study in Almora, Uttarakhand (Meena et al, 2018) also revealed a higher accumulation of SOC, down to a depth of 45 cm, in FLs as compared to cultivated lands. The observed build up of SOC content in the natural grasslands (FL; Figure 2d) could also be due to its continuous incorporation through root litter (Powlson et al, 2022). Additionally, these soils are rarely disturbed by cultural practices that are otherwise followed in orchard soils (e.g., monsoon or winter plowing) of the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Land use and its management not only changes the nutrients' availability (Dad & Abdollahi, 2021; Loria et al, 2016; Silva‐Olaya et al, 2022), their stocks (Chatterjee et al, 2020; Powlson et al, 2022), and stoichiometry (Buchkowski et al, 2019) in soils but also it is equally important to evaluate their impacts on the ability of the soil to function, that is, soil quality (Basak et al, 2021; Bhaduri & Purakayastha, 2014). Some of the soil parameters in these fragile land use systems might reflect an early sign of soil quality deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Janzen et al. (2022) point out that the limit is imposed by photosynthesis; this is true in natural systems and in arable agriculture (Powlson et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Sand particles have a low charge and do not reach. As a result, high-clay soils can contain more cations than low-clay soils [60].…”
Section: Comparison Of Chemical Analyze Of Soil Quality Withmentioning
confidence: 99%